Study on Absolute Positioning Error Compensation for the Drill Rod of the Three-arm Rock-drilling Jumbo - Xia Yimin; Li Zhengguang; Luo Jianli; Ma Jiesong (Jixie chuandong)
In order to improve the absolute positioning accuracy for the drill rod of the three-arm rock-drilling jumbo,firstly,based on the finite element simulation,the main parameters that affect the flexible error of the arm are determined by the orthogonal test method, and the flexible error compensation formula is obtained. Then,after the transformation of the force joint coordinate system,the calibration model is set up based on the kinematics position error,and the redundant parameters are eliminated in the model by redundancy analysis. Finally,the laser total station is used as the measuring device,and the LM algorithm is used to solve the calibration parameters to verify the kinematics calibration effect. The results show that the method effectively compensates the absolute positioning error of the drill rod,the absolute positioning error of the drill rod is reduced by 79. 6%.